1969
DOI: 10.1037/h0028432
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral correlates of perceived leadership.

Abstract: In analyses of transcripts from 108 3-man groups, perceived leaders participated significantly more than nonleaders in production, discussion, and problem solving tasks. With the effect of overall participation partialed out, very few behavioral differences between leaders and nonleaders remained. However, high participation was neither a sufficient nor necessary condition for perceived leadership. High participators, not perceived as leaders, emphasized activities detrimental to group creativity and deemphasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1

Year Published

1975
1975
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 11 publications
2
43
1
Order By: Relevance
“…An interesting aspect of activity level relates to its timing. Morris and Hackman (1969) found that emergent leaders were not only those who expressed more ideas, but also those individuals who initiated the process and asked more questions than others within the group. In text-based VTs, frequency of participation can be measured by the quantity of written interactions, that is, the absolute or relative number of comments per individual in the team (e.g., Bonito, 2000;Straus, 1996).…”
Section: Predicting Transformational Leadership In a Virtual Contextmentioning
confidence: 97%
See 1 more Smart Citation
“…An interesting aspect of activity level relates to its timing. Morris and Hackman (1969) found that emergent leaders were not only those who expressed more ideas, but also those individuals who initiated the process and asked more questions than others within the group. In text-based VTs, frequency of participation can be measured by the quantity of written interactions, that is, the absolute or relative number of comments per individual in the team (e.g., Bonito, 2000;Straus, 1996).…”
Section: Predicting Transformational Leadership In a Virtual Contextmentioning
confidence: 97%
“…For activity level, we followed Morris and Hackman (1969) and Bonito (2000) and flagged initiation of ideas in the VTs by registering a score of "1" in each team for the participant that authored the first meaningful, written utterance, and "0 for the others. We also calculated a percentile for each participant that shows their frequency of participation-the proportion of the total group utterances that was represented by their contribution (see, Mullen, Salas, & Driskell, 1989).…”
Section: Activity Levelmentioning
confidence: 99%
“…Research suggests that task-oriented behaviors are associated with leadership emergence in task-oriented groups (e.g., Carter, Haythorn, Shriver, & Lanzetta, 1951;Kirscht, Lodahl, & Haire, 1959;Morris & Hackman, 1969;Stein & Heller, 1979;Mullen, Salas, & Driskell, 1989), and are perceived as the most appropriate form of leadership behavior under time pressure (Kerr, Schriesheim, Murphy, & Stogdill, 1974). Hence, we chose two task-oriented leadership emergence behaviors to code for.…”
Section: Dependent Variablementioning
confidence: 99%
“…Morris and Hackman (1969) found a significant relationship between participation and leadership. Riecken (1958) found that the more talkative group member was more effective at generating task-oriented solutions.…”
Section: J 20 Navirasyscen Tr87-002mentioning
confidence: 93%